Heinrich Meng papers - Meng, Heinrich, 1887-1972.
Correspondence, notes by Meng on his analytic sessions with Sigmund Freud in January and February 1925, and articles written by Meng, 1951-1958. Correspondence consists primarily of letters to Meng concerning a campaign by Freud associates to have Sigmund Freud awarded a Nobel prize and congratulatory letters on Freud's eightieth birthday in 1936. Correspondents include Albert Einstein, Romain Rolland, Thornton Wilder, and Virginia Woolf.
Physician, psychoanalyst, and educator.
Chiefly photocopies.
In English, German, and French.
Forms part of: Sigmund Freud collection.
Keywords: Einstein, Albert, -- 1879-1955 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Rolland, Romain, -- 1866-1944 -- Correspondence; Wilder, Thornton, -- 1897-1975 -- Correspondence; Woolf, Virginia, -- 1882-1941 -- Correspondence; Psychoanalysis; Educators; Physicians; Psychoanalysts